Do natural landscapes contribute to reducing Land Surface Temperature (LST)? A case study from Muthurajawela wetland, Sri Lanka - Harsha Dahanayake; Deepthi Wickramasinghe; DDGL Dahanayaka (Journal of Degraded and Mining Lands Management, 2022)
Microclimate regulation is one of the most significant ecosystem services provided by wetlands. The present study attempted to investigate the cooling effect provided by Muthurajawela, a coastal Ramsar wetland using Remote Sensing and GIS.  The variation of Land Surface Temperatures (LST) over different land use categories of natural (water bodies, marsh, thick vegetation, grassland) and anthropogenic (built-up areas, coconut cultivations and bare lands) areas in 2015 and 2020. Parameters including Satellite Brightness Temperature, Normalized Difference Vegetation Index, Proportion of Vegetation and Land Surface Emissivity were calculated along eight transects starting from the center of the water body and extending up to 5 km from the boundary of the wetland. The results revealed that LST over areas under natural land cover (2015 - mean 25.040C, 2020 - mean 23.360C) were significantly lower than that of areas under anthropogenic influence (2015 - mean 26.520C and 2020 - mean 26.220C). The lowest increase of LST was over the water body and the highest was over the built-up areas indicating the buffering capacity of wetlands. As air temperatures are highly linked to LST, our findings suggest that wetlands contribute to lower atmospheric temperature and offer cooling effects during dry months. Acknowledging the importance of wetlands in reducing temperature, at least in a local scale, justifies the need of conserving these ecosystems, as seeking mitigatory measures for climate change driven frequent heating effects is challenging.